Immediate and Intermediate-Term Outcomes of Infants With Transposition of Great Arteries Who Underwent Balloon Atrial Septostomy in Sudan - Sulafa K. M. Ali; Amna Elsheikh; Mohammed Abdulrahman Alhassan (Global Heart)
Transposition of great arteries (TGA) is a critical congenital heart disease leading to a fatal outcome if timely management is not provided. Management in low-income countries is challenging. A retrospective analysis was carried out at Sudan Heart Center for infants with TGA who underwent balloon atrial septostomy (BAS) from January 2010 to December 2020. Immediate clinical- and procedure-related outcomes were evaluated. Intermediate-term outcomes were studied using follow-up hospital records as well as direct telephone calls. The study included 75 infants (70% males) with a median age at presentation of 25 and at the time of BAS of 28 days. Pre-BAS median oxygen saturation was 48 (Interquartile Range (IQR) 40–60%). BAS was performed under fluoroscopy and echocardiography guidance with immediate success achieved in 98% of patients. Post-BAS oxygen saturation increased to 87 (IQR 85–90%) with a median improvement of 40% (p = 0.048), which was more significant in those less than 2 weeks of age. Minor complications occurred in 14 patients, and two patients (2.6%) died. Surgery (atrial in 44% and arterial switch operations in 41%) was performed in 39 patients (52%) at a mean age of three months with perioperative mortality of 30%. Infants who underwent surgery had a significantly higher survival rate (69%) compared to those who did not (5.6%) (p < 0.001). Patients with TGA present at a late age with good immediate outcomes of BAS. Access to surgery is limited with a high surgical mortality. Those who survived surgery had good intermediate-term outcomes while most unoperated patients died.